Competitive strategies for academic entrepreneurship : commercialization of research-based products - Karwowski, Waldemar, 1953-; Szopa, Anna, 1982- (Hershey : Business Science Reference, 2015)
'This book seeks to fill the gap in research between universities and the public, and offers cutting-edge insight into the current state of the field, charting a course that moves from discussions of academic resistance and implications for knowledge-transfer theory to current case-studies of academic/industrial launch-pads like COTEC's Technology Commercialization Accelerator and the Maryland Industrial Partnerships program'--
Includes bibliographical references (pages 273-308) and index.
Keywords: Technology transfer -- Economic aspects; University-based new business enterprise; Academic-industrial collaboration